تأثير بعض العوامل البيئية والتقنية في تخطيط المطارات - ديب, عادل (Latakia University Journal -Engineering Sciences Series, 2019)
إن تسليط الضوء على بعض العوامل البيئية والتقنية ودورها في تخطيط المطارات يفرض علينا وضع منهجية هندسية علمية نعتمد عليها في الدراسة والتحليل التي تساعد في التقليل قدر الإمكان من ظهور بعض العيوب أثناء مراحل إنشاء المطار. لقد قمت باستعراض الجوانب المختلفة لتأثير بناء المطارات على البيئة المحيطة كما أجريت دراسة ً تشخيصيةً لتأثير مطار الشهيد باسل الأسد الدولي على الأرض المحيطة حيث يعتبر إيجاد حل لمشكلة الضجيج الجوي أمرا ً ملحا ً جدا ً. كما وضعت مخططا ً يوضح تأثير مناطق الضجيج الجوي وفق مستويات الصوت الأعظمي والمكافئ لمطار الشهيد باسل الأسد، وتوصلت إلى مجموعة من النتائج والتوصيات التي من شأنها تخفيف الأثر السلبي الذي يتركه المطار على المواطنين والبيئة المحيطة. To shed light on some environmental and technical factors and the role they play in planning airports obliges us to devise a scientific engineering approach on which we rely in studying and analyzing. This approach will help us to lessen as possible the defaults that may occur during the stages of constructing an airport. I have displayed the different sides of the effects of building airports on the surrounding environment. I have also made a diagnostic study concerning the effects of the Martyr Bassel Al-Assad’s International Airport on the surrounding area, where finding a solution for the problem of air noise is very urgent. A diagram is drawn to show the effects of air noise areas according to the levels of equivalent and highest sounds at the Martyr Bassel Al-Assad’s Airport. I have attained a range of results and recommendations that can help in alleviating the negative effect that the airport leaves on both the inhabitants and the surrounding environment.